Advanced technologies, systems, and applications IV : proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT 2019) /: proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT 2019). ([2020]) - Unknown
No abstract available